2002
DOI: 10.1152/japplphysiol.00247.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide contributes to 20-HETE-induced relaxation of pulmonary arteries

Abstract: In contrast to its constrictor effects on peripheral arteries, 20-hydroxyeicosatetraenoic acid (20-HETE) is an endothelial-dependent dilator of pulmonary arteries (PAs). The present study examined the hypothesis that the vasodilator effects of 20-HETE in PAs are due to an elevation of intracellular calcium concentration ([Ca(2+)](i)) and the release of nitric oxide (NO) from bovine PA endothelial cells (BPAECs). BPAECs express cytochrome P-450 4A (CYP4A) protein and produce 20-HETE. 20-HETE dilated PAs precons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 32 publications
4
44
1
Order By: Relevance
“…Birks et al (9) have shown that isolated human pulmonary arteries dilate in a dose-dependent fashion to 20-HETE and that microsomes from adult lung have the enzymatic capacity to synthesize 20-HETE from arachidonic acid. 20-HETE relaxes preconstricted isolated rabbit and bovine pulmonary artery rings (34,35). Moreover, inhibition of endogenous 20-HETE release results in increased basal PAP and enhanced vasoconstrictor responses to hypoxia in isolated perfused rabbit lungs, suggesting that release of 20-HETE serves to maintain the low baseline PVR that characterizes the adult lung (35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Birks et al (9) have shown that isolated human pulmonary arteries dilate in a dose-dependent fashion to 20-HETE and that microsomes from adult lung have the enzymatic capacity to synthesize 20-HETE from arachidonic acid. 20-HETE relaxes preconstricted isolated rabbit and bovine pulmonary artery rings (34,35). Moreover, inhibition of endogenous 20-HETE release results in increased basal PAP and enhanced vasoconstrictor responses to hypoxia in isolated perfused rabbit lungs, suggesting that release of 20-HETE serves to maintain the low baseline PVR that characterizes the adult lung (35).…”
Section: Discussionmentioning
confidence: 96%
“…20-HETE causes concentration-dependent relaxation of isolated human adult pulmonary arteries and of adult rabbit pulmonary artery rings (9,21,34). However, in contrast to the fetal lung, myogenic vasoconstriction is not believed to be present in the low-resistance adult pulmonary circulation.…”
mentioning
confidence: 99%
“…Despite these caveats, these data provide critical links of 20-HETE-induced NO release from BPAECs (36).…”
mentioning
confidence: 91%
“…Superoxide is rapidly dismutated to hydrogen peroxide, which then mediates activation of PI3-kinase/Akt, phosphorylation of eNOS, and enhanced release of NO from eNOS in response to 20-HETE in BPAECs. pulmonary endothelium; superoxide; hydrogen peroxide; endothelial nitric oxide synthase WE HAVE PREVIOUSLY DEMONSTRATED that 20-HETE, a product of arachidonic acid catalyzed by CYP4, induces activation of nitric oxide synthase (NOS) from pulmonary artery endothelial cells in a [Ca 2ϩ ] i -dependent manner (9,23,36). Furthermore, 20-HETE releases NO, which contributes to endotheliumdependent vasodilation in pulmonary arteries (9, 19).…”
mentioning
confidence: 99%
“…However, this molecule is formed by the same pathway as leukotrienes, and shares structural similarities with both EETs and 20-HETE all of which are known for their ability to modulate vascular (34,40) and airway smooth muscle tone (3,6,36) in asthma, chronic obstructive pulmonary disease, and acute respiratory distress syndrome patients. Alteration of bronchial wall reactivity to various eicosanoids and cytokines is a characteristic feature of chronic asthma.…”
mentioning
confidence: 99%